Implementation Of Online Annual Motor Vehicle Tax Payment Services In The Cibadak Samsat Area, Sukabumi Regency - Cecep Wahyudin (Journal of Multidisciplinary Science, 2022)
The purpose of this study was to determine the implementation of the annual online motor vehicle tax payment service in the Cibadak Samsat area, Sukabumi Regency. This study uses a descriptive method with a qualitative approach. The research focus is based on the implementation theory of based on two dimensions, namely the dimensions of standards and policy objectives and the dimensions of communication between organizations. The respondents of this research are motor vehicle taxpayers and employees related to the researcher. The main instrument in data collection is in the form of questionnaires, and interviews and also assisted with observations and documentation/libraries. Data analysis used the Weight Mean Score formula to use the average score. The results of the study show that the implementation of the annual online PKB payment service has been going well. This can be seen from the application of online PKB payment services through the J'Bret Samsat program that is in accordance with policy standards and targets which can make taxpayers feel easy, fast, safe, transparent, and timely in making annual PKB payments so that taxpayers do not need to worry about delays in annual PKB payments when the taxpayer is in a different city. However, it was found that there are still not so many taxpayers who use online PKB payment services because there are still obstacles to its implementation.